2021
DOI: 10.1182/bloodadvances.2020003858
|View full text |Cite
|
Sign up to set email alerts
|

Precocious clonal hematopoiesis in Down syndrome is accompanied by immune dysregulation

Abstract: Key Points Children with Down syndrome develop early signs of clonal evolution that resemble traditional clonal hematopoiesis. Children with trisomy 21 who exhibit clonal hematopoiesis display cytokine and gene expression profiles indicative of disrupted immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…It is also possible that the development of mutant clones requires a prolonged timeframe, beyond the typical lifespan of HGPS patients, even in conditions of accelerated aging and abnormal hematopoiesis. In agreement with our findings in HGPS children, absence of CHIP with VAF ≥ 2% was also revealed in deep sequencing studies of other young cohorts, including Down syndrome individuals and childhood cancer survivors [24,25], and only one mutation was identified by whole exome sequencing in a non-cancer cohort of 388 children [26]. These findings reinforce the relevance of time for the expansion of mutant clones that acquire a selective advantage, supporting the association of CHIP with chronological aging and emphasizing the differences between chronological aging (merely reflecting the time passed since birth) and biological aging (the decline over time in tissue and organismal function), which is exaggerated in HGPS patients.…”
Section: Abstract Somatic Mutations • Premature Aging Syndrome • Chip...supporting
confidence: 92%
“…It is also possible that the development of mutant clones requires a prolonged timeframe, beyond the typical lifespan of HGPS patients, even in conditions of accelerated aging and abnormal hematopoiesis. In agreement with our findings in HGPS children, absence of CHIP with VAF ≥ 2% was also revealed in deep sequencing studies of other young cohorts, including Down syndrome individuals and childhood cancer survivors [24,25], and only one mutation was identified by whole exome sequencing in a non-cancer cohort of 388 children [26]. These findings reinforce the relevance of time for the expansion of mutant clones that acquire a selective advantage, supporting the association of CHIP with chronological aging and emphasizing the differences between chronological aging (merely reflecting the time passed since birth) and biological aging (the decline over time in tissue and organismal function), which is exaggerated in HGPS patients.…”
Section: Abstract Somatic Mutations • Premature Aging Syndrome • Chip...supporting
confidence: 92%
“…Individuals with T21 demonstrate presence of clonal haematopoiesis at higher frequency and younger age compared to disomic individuals. 7 Haematopoetic stem cells, differentiated lymphocytes and mononuclear cells from individuals with T21 display defective DNA repair mechanisms and increased sensitivity to oxidative damage, contributing to a state of genomic instability. 8 , 9 Increased expression of DYRK1A , located on chromosome 21, in haematopoietic cells caused significant derangement of DNA damage repair pathways in T21-derived induced pluripotent stem cell (iPSC) models, giving a possible mechanism for genome instability in T21.…”
Section: Role Of T21 In Leukaemogenesismentioning
confidence: 99%
“…10 , 11 In this way, T21 provides a microenvironment conducive to expansion of clonal populations and the acquisition of oncogenic mutations. 7 Single-cell studies have demonstrated increased mutagenesis in T21 foetal haematopoietic stem cells, leading to an increased risk of acquiring additional leukaemogenic mutations. 12 …”
Section: Role Of T21 In Leukaemogenesismentioning
confidence: 99%
“…RNA-seq was done as previously described ( 66 ). Briefly, peripheral blood was collected from human study participants in PAXgene RNA Tubes (PreAnalytiX/Qiagen, Cat# 762165).…”
Section: Supplementary Materials Formentioning
confidence: 99%